The Impact of Green Accounting Implementation and Environmental Performance on the Performance of Manufacturing Companies Listed on the IDX in 2022–2024 - Dwi Nur Isra; Amira Fauziah; Nurhalizah; Muchriana Muchran (IECON: International Economics and Business Conference, 2025)
This study aims to examine the effect of green accounting implementation and environmental performance on the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The approach used is quantitative with a causal research type. The research sample consisted of 30 manufacturing companies selected using the purposive sampling method, with secondary data obtained from annual reports and sustainability reports. The independent variables analyzed were green accounting and environmental performance (measured through PROPER), while company performance was measured using Return on Assets (ROA). The results of the study indicate that green accounting partially and simultaneously has a positive and significant effect on the company's ROA, while environmental performance does not have a significant effect on the company's ROA. These findings confirm that the integration of environmental aspects into the company's accounting and operational reporting systems can strengthen social legitimacy and increase efficiency and profitability.